MANAJEMEN DESA DALAM MEMBANGUN KESADARAN MASYARAKAT TERHADAP RISIKO BENCANA (STUDI KASUS PAYA TUMPI BARU ) - Insani Ulfa; Makmur Jaya; Hamdan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze village management practices in building disaster-aware community consciousness in Paya Tumpi Baru Village, Kebayakan District, Central Aceh Regency, through an Islamic community development approach, specifically identifying village management practices and examining the challenges encountered. The research employs a descriptive method with a qualitative approach, using observation, semi-structured interviews with 3–5 informants (the village head, village officials, religious leaders, and residents), and documentation as data collection techniques. The findings reveal that the village government successfully transformed theological values such as ukhuwah islamiyah (social solidarity), taqwa (spiritual vigilance), and fardhu kifayah (collective responsibility) into a planned disaster risk management system, with meunasah (prayer halls) and mosques functioning as centers for education and early warning dissemination. This participatory management model proved effective in shifting the community's paradigm from passive-reactive to active-preventive. The study concludes that disaster risk mitigation in the village is effective when village governance is integrated with Islamic community development values, resulting in an inclusive, self-reliant, and resilient community ecosystem.